Respuesta :
Just substitute 4 for x in the given equation:
h(4) = 3^4 - 7 = 81 - 7 = 74 (answer)
h(4) = 3^4 - 7 = 81 - 7 = 74 (answer)
h(x) = (3^x) - 7
h(4) = (3^4) - 7 ... replace every x with 4; then use PEMDAS to simplify
h(4) = 81 - 7
h(4) = 74
Answer: 74
Side Note: 3^4 means we have four copies of '3' being multiplied together
3^4 = 3*3*3*3 = 9*9 = 81
h(4) = (3^4) - 7 ... replace every x with 4; then use PEMDAS to simplify
h(4) = 81 - 7
h(4) = 74
Answer: 74
Side Note: 3^4 means we have four copies of '3' being multiplied together
3^4 = 3*3*3*3 = 9*9 = 81